DEVELOPMENT OF LEXICAL-GRAMMATICAL PART OF CHILD SPEECH AT FRONTAL CLASSES OF SPEECH THERAPY IN SHORT-STAY GROUPS - Tatiana S. Shehovtsova; Natalia M. Borozinets (Вестник Северо-Кавказского федерального университета, 2022)
The item offers a view at an experimental research aiming at detecting and testing the conditions for successful speech therapy for developing lexical-grammatical speech in children suffering from general speech delay through preschool training.